Lung cancer survival among never smokers. (1st June 2019) - Casal-Mouriño, Ana; Valdés, Luis; Barros-Dios, Juan Miguel; Ruano-Ravina, Alberto
Abstract: Lung cancer incidence among never smokers has increased in recent decades with 10–30% of all lung cancers occurring in never smokers, where exposure to residential radon is the leading cause of this disease. Lung cancer survival is low, ranging from 12% to 16% at 5 years of diagnosis. There is scant evidence to date on survival from this disease in never smokers. We aim to evaluate lung cancer survival in never smokers and ascertain whether there might be differences regarding smokers, through a systematic review applying predefined inclusion and exclusion criteria. 17 Studies were included. Never-smoker lung cancer patients seem to experience longer survival times than do smokers or ex-smokers. Lung cancer in never smokers displays distinctive clinical characteristics, is more frequent among women, is diagnosed at more advanced stages, and the predominant histologic type is adenocarcinoma. Further studies are necessary to ascertain lung cancer survival among never smokers. Highlights: Never-smoking lung cancer patients seem to experience longer survival smokers or ex-smokers. Mean overall survival for never-smokers ranges from 7.7 to 44.6 months. Lung cancer in never smokers is diagnosed at more advanced stages, and adenocarcinoma is the most frequent histological type. Further studies are necessary to ascertain lung cancer survival among never smokers.